Industrial propagation of Dendrobium sp., Phalaenopsis sp., Cymbidium sp. and Rhynchostylis sp. by immersion bioreactor technique - Phuong Hoa, Mai Thi; Tuong Thu, Bui Thi; Minh, Tran Van (Academia Journal of Biology, 2012)
Protocorm like bodies (PLB) were used as planting materials. The basic favored agar-medium for PLB micropropagation plantlet growth to Dendrobium sp. was MS (M.0244), same as Vacine-Went (V.0226) to Phalaenopsis sp., Orchimax (O.0257) to Cymbidium sp. and Lindemann (L.0216) to Rhynchostylis sp. On the media for micropropagation of phalaenopsis and cymbidium enhance protocorm initiation (6.8 and 8.2 PLB/chuster) and shoot regeneration (2.6 and 2.4 shoots/cluster). In reverse, Dendrobium sp. and Rhynchostylis sp. were forwarded to shoot regeneration (2.6 and 2.4 shoots/cluster). The rhythm for immersion bioreactor cultures was sinking and floating in 1 minute/4 hours to proliferate, regenerate and grow of PLB and plantlets. Dendrobium sp. was favored to micropropagation of shoots (6.6 shoots/cluster) and plant growth (45 mm length of leaves). Phalaenopsis sp. was favored for micropropagation of protocorm (5.8 PLB/cluster), shoots (2.8 shoots/cluster) and plant growth (38 mm length of leaves). The same as to Cymbidium sp. and Rhynchostylis sp. in micropropagation of protocorm (6.8 and 2.2 PLB/cluster), shoots (3.2 and 2.6 shoots/cluster) and plant growth (48 and 24 mm length of leaves). It’s supplemented with 2‰ PPM to media culture to limit the PLB and shoots decayed by infected of microbes, enhanced shoots initiation (6.2 shoots/cluster) and favored to plant growth (38 mm length of leaves). Micropropagation of Dendrobium sp., Phalaenopsis sp., Cymbidium sp. and Rhynchostylis sp., by immersion bioreactor technique was established up.